Anti-tumor effect of Huayu Jiedu formula on SGC-7901 cancer cell (Bangladesh Journal of Pharmacology, 2016)
In this study, we evaluated the effects of the extract of Huayu Jiedu (HYJD) formula on anti-tumor activity. It was found that HYJD treatment inhibited proliferation of seven cancer cell lines (IC50: 1.23-6.23 mg/mL). The gastric cancer cell line SGC-7901 was the most sensitive to HYJD. HYJD inhibited SGC-7901 cells proliferation in a dose- and time-dependant manner. More-over, HYJD significantly inhibited SGC-7901 cells adhesion, invasion and migration in a dose-dependent manner. qPCR results showed that HYJD treatment had no effect on PI3K, PDK1 and Akt mRNA expression. However, HYJD dramatically down-regulated Akt phosphorylation through inhibition of PDK1 kinase activity. Importantly, HYJD inhibited growth of tumor xenografts with no effect on body weight and spleen index. HYJD also significantly down-regulated Akt phosphorylation in tumor tissue. Taken together, this study demonstrated that HYJD exhibited an anti-tumor property, suggesting that HYJD may be a potential drug in the treatment of cancer.